Improvement of Metadiscourse Use among Iranian EFL Learners through a Process- based Writing Course - Mansoor Tavakoli; Leila Bahrami; Zahra Amirian (Journal of English Language Teaching and Learning, 2012)
The present study investigated the use of interactive metadiscourse resources (IMRs) in terms of appropriacy during a process- based writing course by applying qualitative and exploratory methods. Moreover, learners' perception was investigated to find out how confident they felt as they were writing and rewriting the drafts. 30 intermediate EFL learners were chosen to participate in this study based on their performance on the OPT. The participants wrote essays on argumentative topics during the period of one semester. Each participant submitted three drafts on a topic, the first draft, the draft after revising and the draft after editing.  Experts’ appropriacy judgments showed a clear improvement in the appropriate use of IMRs from the participants’ earlier drafts to their final drafts. Furthermore, analysis of the interviews’ data showed that most of the interviewees had positive views towards this kind of writing and stated that their level of confidence in using IMRs increased through the stages and they felt more confident towards the end of the course. The results of this study seem to have some implications for teachers and practitioners in EFL contexts and could be of major significance for classroom application.